METODE AL-MIFTAH LI AL-ULUM: ALTERNATIF PEMBELAJARAN KITAB KUNING PADA PENDIDIKAN DINIYAH FORMAL - Muslihin Sultan; M. Yahya (Institut Agama Islam Negeri (IAIN) Bone, 2020)
This paper focuses to describe the implementation of al-Miftah learning method as an alternative way to read the yellow book for PDF students. This research is field research with descriptive qualitative type. Data was collected by employing observation, interviews, and documentation techniques. The collected data were then analyzed through data reduction, data display, data verification, and drawing conclusions. The research finding shows that the implementation of al-Miftah method brings positive experience for students. Learning nahwuaraf using al-Miftah material is very good for beginners, because it focuses on recognizing and identifying word for word in Arabic. The main advantage of al-Miftah method is the aspect of learning density. Al-Miftah method could briefly cover almost all nahwu-sharaf materials and identify different types of words among letters, isim, and fi'il. Furthermore, al-Miftah includes the memorable songs in the form of reading nazam to help students easier to practice reading the yellow book. On the other hand, it is quite hard for students to master the very dense material in a short time.Keywords: al-Miftah li al-Ulum; arabic reading method; reading yellow book.